2003
DOI: 10.1677/erc.0.0100375
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between radiation and endocrine therapy in breast cancer.

Abstract: Adjuvant radiotherapy and adjuvant endocrine therapy are commonly given to patients with invasive breast cancer or with ductal carcinoma in situ (DCIS). Although both therapies have been well established through a number of randomized studies, little is known about a possible interaction of both treatment modalities if they are given simultaneously. A number of in vitro studies have indicated that tamoxifen treatment might reduce the intrinsic radiosensitivity of MCF-7 breast cancer cells. Conversely, estradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 117 publications
1
25
0
2
Order By: Relevance
“…Although some in vitro experiments [32][33][34] demonstrated a decreased sensitivity to ionizing radiation after incubation of MCF-7 cell lines with tamoxifen, an antagonistic effect of ionizing radiation and treatment with tamoxifen has not been confirmed in animal studies [35,36]. In contrast, several large randomized clinical studies [37] comparing adjuvant tamoxifen, radiation therapy and placebo, and combined radiation therapy and tamoxifen demonstrated best results [38]. Thus, the experimental endpoints of the in vitro studies may not have been relevant for the in vivo situation, and there is no clinical data for an adverse effect of combined tamoxifen and radiation.…”
Section: Combining Irradiation and Systemic Therapymentioning
confidence: 99%
“…Although some in vitro experiments [32][33][34] demonstrated a decreased sensitivity to ionizing radiation after incubation of MCF-7 cell lines with tamoxifen, an antagonistic effect of ionizing radiation and treatment with tamoxifen has not been confirmed in animal studies [35,36]. In contrast, several large randomized clinical studies [37] comparing adjuvant tamoxifen, radiation therapy and placebo, and combined radiation therapy and tamoxifen demonstrated best results [38]. Thus, the experimental endpoints of the in vitro studies may not have been relevant for the in vivo situation, and there is no clinical data for an adverse effect of combined tamoxifen and radiation.…”
Section: Combining Irradiation and Systemic Therapymentioning
confidence: 99%
“…Although some experimental data suggest that tamoxifen might decrease radiation sensitivity of breast cancer cells in vitro, clinical data do not substantiate this observation [63,64]. Moderately increased risks for late pulmonary damage and subcutaneous fibrosis have been reported at least for subsets of patients [65,66].…”
Section: Adjuvant Endocrine Treatmentmentioning
confidence: 99%
“…This block would be augmented by tamoxifen and antagonized by estrogen, since the latter would induce cell proliferation by antagonizing the G1 block. Experimental findings are summarized in table 1 and have been reviewed in detail elsewhere [1]. Most of the studies found a synergistic or additive interaction of estradiol and XRT, and an antagonistic interaction of tamoxifen and XRT.…”
Section: In Vitro Experiments On the Interaction Of Estrogens Antiesmentioning
confidence: 99%
“…Recent clinical studies in ductal carcinoma in situ showed a positive effect of the combined treatment with tamoxifen and XRT on local recurrence-free survival. Due to these conflicting results, clinicians are often uncertain as to how to combine both treatment modalities [1]. This review will summarize the in vitro studies on the interaction of endocrine therapy and XRT in tumor cells and in nonmalignant tissues.…”
Section: Introductionmentioning
confidence: 99%